Employees' perspective of ethics in Malaysia / Rabiatul Alawiyah Zainal Abidin, Raziah Bi Mohamed Sadique and Norhayati Alias - Zainal Abidin, Rabiatul Alawiyah; Mohamed Sadique, Raziah Bi; Alias, Norhayati (Research Management Institute (RMI), 2011)
The aim of this study is to explore the perception and understanding of employees towards companies/organizations code of conduct and ethics program. The increasing number of companies' collapses in the recent years has triggered the need to understand why it happened. The blame falls on the poor economic performance and corporate fraud or misconduct. The later reason is the most alarming and threatening. It threatens the economy as well as social stability of a country. One of the major contributors to fraud activities is poor ethical values among company's employees. This has forced companies to have a proper code of conduct and ethics programs to ensure that employees are aware that to work ethically is important for the companies. It is important for companies to have a proper and effective code of conduct and ethics program and is saying so, the employees should be able to understand and familiar with it to ensure the effectiveness of the code and ethics programs. Questionnaires were distributed to a sample of companies/organizations in the Klang Valley which asked on the perception of employees towards companies/organizations code of conduct and ethics program. The results indicates that majority of companies/organization surveyed do have code of conduct and ethics programs. It is also found out that majority of the employees understand the code and ethics programs, know the purpose and indicates that managers pay serious attention to ethics. Apart from a small percentage of respondents that did not understand or are not clear with the code and ethics programs, it can be said that overall attitude towards ethics is very good. It was also found out that less than 50% of the respondents are familiar with the purpose of ethics program which could be an area of improvement to companies/organizations as it is vital for employees to understand the purpose of ethics program in order for it to be effective and achieve its goal.